2020
DOI: 10.1038/s41598-020-74012-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced resting state functional connectivity with increasing age-related hearing loss and McGurk susceptibility

Abstract: Age-related hearing loss has been related to a compensatory increase in audio-visual integration and neural reorganization including alterations in functional resting state connectivity. How these two changes are linked in elderly listeners is unclear. The current study explored modulatory effects of hearing thresholds and audio-visual integration on resting state functional connectivity. We analysed a large set of resting state data of 65 elderly participants with a widely varying degree of untreated hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Increased task-modulated functional connectivity between auditory and visual cortex -when comparing incongruent (McGurk) with congruent audiovisual stimuli -was found in hard-of-hearing compared to normal-hearing participants (Rosemann et al, 2020). Moreover, increased McGurk illusions were correlated with decreased resting state functional connectivity between auditory and motor regions in mild to severe hard-of-hearing individuals (Schulte et al, 2020). Thus, previous research provided evidence for changed audiovisual integration abilities in age-related hearing loss, and functional connectivity alterations in the auditory cortex associated with the McGurk illusion.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Increased task-modulated functional connectivity between auditory and visual cortex -when comparing incongruent (McGurk) with congruent audiovisual stimuli -was found in hard-of-hearing compared to normal-hearing participants (Rosemann et al, 2020). Moreover, increased McGurk illusions were correlated with decreased resting state functional connectivity between auditory and motor regions in mild to severe hard-of-hearing individuals (Schulte et al, 2020). Thus, previous research provided evidence for changed audiovisual integration abilities in age-related hearing loss, and functional connectivity alterations in the auditory cortex associated with the McGurk illusion.…”
Section: Introductionmentioning
confidence: 89%
“…We further used the M1 lip area as a ROI because its neural activity was shown to be related to the McGurk illusion in healthy volunteers (Murakami et al, 2018). Further, studies in age-related hearing loss demonstrated increased neural activity in motor cortex but decreased coupling between auditory and motor regions with increased McGurk illusion responses (Rosemann et al, 2020;Schulte et al, 2020). The ROI in the left and right fusiform gyrus was provided by the atlas implemented in CONN.…”
Section: Analysis Of Mri Datamentioning
confidence: 99%
See 1 more Smart Citation
“…106 This finding is consistent with past findings that indicate increased frontal recruitment in hearing-impaired individuals as a compensatory mechanism to control for reduced auditory inputs. 107 Studies also demonstrate decreased brain functional connectivity between the dorsal attentional network (DAN) and sensorimotor and motor regions, 108,109 as well as between the SN and the visual cortex in ARHL, 109 which can affect attentional, visual, sensorimotor, and motor processes.…”
Section: Resting-state Fmrimentioning
confidence: 99%
“…In addition to MRI studies on the local brain regions of patients with ARHL, the whole-brain functional network’s research deserves further discussion. An MRI study on the functional connectivity of the resting state of 65 patients with ARHL found that a higher degree of hearing loss was significantly associated with decreased resting-state functional coupling, and the connectivity of the dorsal attention network gradually decreased with an increase in the hearing loss degree (Schulte et al, 2020 ). The connectivity of the dorsal attention network increases when performing tasks requiring attention and responding to stimuli (Corbetta and Shulman, 2002 ).…”
Section: Cognitive Screening Tools Overviewmentioning
confidence: 99%